ECONOMIC VALUE OF BIODIVERSITY AS A PRODUCTION RESOURCE - Zheliazkov, George; Zaimova, Darina (Economics of Agriculture, 2012)
In the last few years the interest towards sustainable development issues and management of biodiversity has rapidly reached global dimensions and undergone changes with meaty character. One of the main reasons for this is the changed proportion between economic purposes and interests; the wider span of ecological priorities; and preserving breeds, which represent society interest and have potential for market demand. The goal of the present study is twofold: to utilize conceptual framework of the business related to biodiversity preserving; and to analyze the economic value and market effect of biodiversity as a production resource. A special attention is given to the balance between economic and market growth, and the system of financial stimuli for those economic subjects whose economic activity and private consumption implies the two sustainability criteria: ecology and social equity.